2015
DOI: 10.1111/bju.13099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between illness uncertainty, anxiety, fear of progression and quality of life in men with favourable‐risk prostate cancer undergoing active surveillance

Abstract: Objectives To evaluate prospectively the associations between illness uncertainty, anxiety, fear of progression, and general and disease-specific quality of life (QOL) in men with favorable risk prostate cancer undergoing active surveillance (AS). Patients and Methods After meeting stringent enrollment criteria for an AS cohort study at a single tertiary care cancer center, 180 men with favorable-risk prostate cancer completed questionnaires at enrollment and every 6 months for up to 30 months. Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 54 publications
5
103
1
2
Order By: Relevance
“…In the current study, a 10 point increase in the mental or physical HRQoL of one spouse was associated with an increase in HRQoL ranging from 0.7 to 1.2 points in the other spouse, while reporting depressed mood was associated with a 2.4 to 4.3 point change in spousal HRQoL. Although these effects are objectively small (with effect sizes ranging from <0.10 to 0.39 [29]), they are akin to the associations with HRQoL (measured, as in this study, with the SF-12 or SF-36) reported for illness uncertainty (Betas≈0.1 [30]), having a greater number cancer-related symptoms (Betas ranging from −0.34 to −0.51 [31]), increasing physical activity after diagnosis (Beta=3.28 [32]), and the longitudinal effect of cancer treatment on HRQoL (Beta=−2.26 [33]). This supports the clinical relevance of change in HRQoL related to spillover from the spouse.…”
Section: Discussionmentioning
confidence: 55%
“…In the current study, a 10 point increase in the mental or physical HRQoL of one spouse was associated with an increase in HRQoL ranging from 0.7 to 1.2 points in the other spouse, while reporting depressed mood was associated with a 2.4 to 4.3 point change in spousal HRQoL. Although these effects are objectively small (with effect sizes ranging from <0.10 to 0.39 [29]), they are akin to the associations with HRQoL (measured, as in this study, with the SF-12 or SF-36) reported for illness uncertainty (Betas≈0.1 [30]), having a greater number cancer-related symptoms (Betas ranging from −0.34 to −0.51 [31]), increasing physical activity after diagnosis (Beta=3.28 [32]), and the longitudinal effect of cancer treatment on HRQoL (Beta=−2.26 [33]). This supports the clinical relevance of change in HRQoL related to spillover from the spouse.…”
Section: Discussionmentioning
confidence: 55%
“…While evidence is still accumulating regarding the association between anxiety/distress and placement onto active surveillance for prostate cancer and what specific factors ultimately lead to a stronger relationship, there is a good deal of research that supports this association and suggests next steps are to implement behavioral and psychosocial interventions. Based on these pilot findings, future studies should examine the efficacy of mindfulness training on both positive and negative psychological responses to active surveillance, as well as its potential association with adherence to active surveillance, especially within larger, more geographically representative samples of men.…”
Section: Resultsmentioning
confidence: 99%
“…A study published since we conducted the searches for our present review used EPIC and SF-12 data for USA men with low-risk prostate cancer undergoing active surveillance [77]; more such studies are required. Although there have been claims that robot-assisted or laparoscopic RP might have reduced impact on symptomatic outcomes, the overall summary of results in the present review did not show this, and this was further confirmed in a recent review of best practice in RP, which revealed that incontinence and erectile dysfunction remained significant factors [78], with urinary incontinence still an important issue 60 months after robotassisted RP, and rates of sexual dysfunction remaining comparable to open RP [57].…”
Section: Discussionmentioning
confidence: 99%